Charging behavior and energy use for 15 electric vehicles in two-car households in the Gothenburg region - Bohlin, Oskar; Kaese, Laura-Marie (My University, 2017)
Conventional vehicles burning fossil fuels are emitting CO2 emissions contributing to climate change. Therefore, electric vehicles are becoming more and more an area of interest due to the need of lowering the CO2 emissions from transportation. This development goes hand in hand with the rising awareness of greenhouse gas (GHG) emissions. The Swedish government has set a goal to have a fossil independent vehicle fleet by 2030, and since analysis made by the IEA indicates that the number of electric vehicles (EVs) are growing in the country and globally, EVs will probably play a big role going there. Moreover, almost all major car producers have EV models and are investing in further research. In this thesis we have analyzed driving and charging data for 15 EVs, all of them were Volkswagen e-golf vehicles situated in Gothenburg, Sweden. The data sets have been collected during the two time periods 1st of October to 22nd of January, and 11th of Febrauray to 30th of May by the division of physical resource at Chalmers university of technology. Our analysis focuses on driving and charging behaviour, including calculations of the energy consumption from both driving and charging the EVs. In order to analyze the behaviours of the test drivers using the EVs, we have looked into how the EVs have been driven through following parameters: number of trips; distance; as well as how, where and how much they have been charged. The results show clearly that the different EV test drivers, included in this study, have different driving behaviours, which, for example, resulted in a broad range of energy consumptions when driving. We also saw that there were variations in energy consumption over periods of time, indicating that the drivers were able to handle seasonal variations differently. It could be concluded that the charging load curves for the EVs showed strong tendencies towards charging in the afternoon, directly at upon home coming. Furthermore, we also saw that all of EVs 1-5 and six of EVs 6-15 were charged simultaneously during the maximum day of energy demand. In addition to this it can be concluded that the analysis of possible shifting of charging showed a big potential for cost savings of about 30 to 50 % during both test periods.
Keywords: Hållbar utveckling; Annan naturvetenskap; Sustainable Development; Other Natural Sciences